2019
DOI: 10.3390/atmos10090548
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Accuracy Assessment of MODIS C6.1 Aerosol Products over the Heavy Aerosol Loading Area

Abstract: The aim of this study is to evaluate the accuracy of MODerate resolution Imaging Spectroradiometer (MODIS) aerosol optical depth (AOD) products over heavy aerosol loading areas. For this analysis, the Terra-MODIS Collection 6.1 (C6.1) Dark Target (DT), Deep Blue (DB) and the combined DT/DB AOD products for the years 2000–2016 are used. These products are validated using AErosol RObotic NETwork (AERONET) data from twenty-three ground sites situated in high aerosol loading areas and with available measurements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…However, with a focus on storm episodes of mineral dust over four sunphotometer ground-based sites in Australia, Mukkavilli et al [49] found overestimation in MEERA-2 AOD. In addition, with respect to MODIS DB/DT and DT algorithms in comparison with AERONET, significant overestimations in AOD were found by Shaheen et al [41] and Tian et al [50], respectively. A larger deviation in RMB is found in the present study for MODIS than MERRA-2, with respect to both monthly and daily averaging (Figure 1).…”
Section: Time Series Of Modis Merra-2 and Aeronet Aomentioning
confidence: 93%
“…However, with a focus on storm episodes of mineral dust over four sunphotometer ground-based sites in Australia, Mukkavilli et al [49] found overestimation in MEERA-2 AOD. In addition, with respect to MODIS DB/DT and DT algorithms in comparison with AERONET, significant overestimations in AOD were found by Shaheen et al [41] and Tian et al [50], respectively. A larger deviation in RMB is found in the present study for MODIS than MERRA-2, with respect to both monthly and daily averaging (Figure 1).…”
Section: Time Series Of Modis Merra-2 and Aeronet Aomentioning
confidence: 93%
“…Compared to Aqua MODIS, Terra MODIS shows better agreement with the ground observation which is indicated by the higher R 2 value. The evaluation of these products over other areas in the Asian region show results with lower R 2 values (Bilal et al, 2018;Huang et al, 2020;Sharma et al, 2021;Tian and Gao, 2019). This may be attributed to the lower number of data samples in the present study, and the difference in the spatial and temporal window size taken for collocation.…”
Section: Accepted Manuscriptmentioning
confidence: 62%
“…Comparison between AOD obtained from satellite-borne (MODIS and CALIOP) and ground-based remote sensing instruments (Lidar) revealed very good consistency 23 . Several studies already reported good consistency between the MODIS AOD and AOD obtained from AERONET measurements 48,49 . We further compared MODIS AOD with the AERONET observations over Kanpur (26.5° N, 80.2° E) where continuous observations are available during 2000-2018 and is shown in Supplementary Fig.…”
Section: Methodsmentioning
confidence: 75%